1997
DOI: 10.1007/s001250050715
|View full text |Cite
|
Sign up to set email alerts
|

Insulin mediators in man: effects of glucose ingestion and insulin resistance

Abstract: Insulin generates/releases chemical substances that alter the activities of purified enzymes [1,2] and the metabolism of intact cells [3,4] in an insulin mimetic fashion. These substances have therefore been termed mediators or second messengers of insulin [5]. Two different insulin mediators have been separated from rat liver [6]. These mediators have been identified as inositol phosphoglycans (IPGs), containing inositol, non-acetylated amino sugars, neutral sugars, ethanolamine, phosphate and, possibly, amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0
1

Year Published

1998
1998
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 27 publications
1
35
0
1
Order By: Relevance
“…They further found that in women with PCOS during a glucose tolerance test there was a three-fold decrease in the release of the chiro-inositol glycan compared with control subjects. Similar findings were reported by Shashkin et al in type II diabetic patients compared with control subjects (61). Scoscia et al studied placental membranes from women with preeclampsia, a disease with insulin resistance, compared with controls (60).…”
Section: Inositol Imbalance and Insulin Resistancesupporting
confidence: 74%
“…They further found that in women with PCOS during a glucose tolerance test there was a three-fold decrease in the release of the chiro-inositol glycan compared with control subjects. Similar findings were reported by Shashkin et al in type II diabetic patients compared with control subjects (61). Scoscia et al studied placental membranes from women with preeclampsia, a disease with insulin resistance, compared with controls (60).…”
Section: Inositol Imbalance and Insulin Resistancesupporting
confidence: 74%
“…Extensive examination of CYP17A1 and CYP11A1 gene expression in normal and PCOS theca cells has revealed that increased CYP17 and myo-inositol to chiro-inositol epimerase activity and a decreased myo-inositol to chiro-inositol ratio. In all previous papers, we have provided evidence for decreased epimerase activity and increased myo-inositol to chiro-inositol ratios in cases of insulin resistance [7][8][9][10][11][12][13][14][15][16]. Our experiments do not shed light on the continuing enigma of the primacy of increased testosterone versus the peripheral insulin resistance as the initiating event in PCOS.…”
Section: Discussionmentioning
confidence: 51%
“…In addition, deficiency of chiro-inositol in urine of Japanese subjects has been demonstrated to be linearly related to insulin resistance in type 2 diabetics, subjects with impaired glucose tolerance and normal subjects [10]. Further, lack of appearance of chiro-inositol glycan bioactivity (measured as PDH phosphatase (PDHP) activity) in blood of type 2 diabetic subjects during a glucose tolerance test, lack of chiro-inositol glycan bioactivity in women with PCOS during an insulin clamp, and lack of appearance of chiro-inositol glycan bioactivity release from placental membranes with insulin administration in vitro in women with preeclampsia have also been shown [11][12][13]. One glycan isolated from beef liver, named INS-2, has been identified, structure determined and chemically synthesized.…”
mentioning
confidence: 96%
“…18 P-IPG seems to play an important role in mediating the insulin effects on peripheral glucose use under physiological conditions, whereas a lack in generation/release of this molecule has been suggested to underlie insulin resistance in noninsulin-dependent diabetic men. 19 We have reported recently an increased urinary excretion of this molecule during pregnancy compared with nonpregnant women with a particularly high concentration in the amniotic fluid in healthy pregnancies. 20 P-IPG production was enhanced by active PE as demonstrated by an increased content or release of this molecule in placentas or fluids (amniotic fluid and urine) of women with this syndrome.…”
Section: Discussionmentioning
confidence: 95%